The semantic web: research and applications 8th Extended Semantic Web Conference, ESWC 2011, Heraklion, Crete, Greece, May 29 - June 2, 2011 :proceedings. - Antoniou, G. (Grigoris) (Lecture Notes in Computer Science, 2011)
The books (LNCS 6643 and 6644) constitute the refereed proceedings of the 8th European Semantic Web Conference, ESWC 2011, held in Heraklion, Crete, Greece, in May/June 2011. The 57 revised full papers of the research track presented together with 7 PhD symposium papers and 14 demo papers were carefully reviewed and selected from 291 submissions. The papers are organized in topical sections on digital libraries track; inductive and probabilistic approaches track; linked open data track; mobile web track; natural language processing track; ontologies track; and reasoning track (part I); semantic data management track; semantic web in use track; sensor web track; software, services, processes and cloud computing track; social web and web science track; demo track, PhD symposium (part II).